Human cytomegalovirus UL40 signal peptide regulates cell surface expression of the NK cell ligands HLA-E and gpUL18 - Prod'homme, Virginie; Lemberg, Marius (The journal of immunology, 2012)
Human CMV (HCMV)-encoded NK cell-evasion functions include an MHC class I homolog (UL18) with high affinity for the leukocyte inhibitory receptor-1 (CD85j, ILT2, or LILRB1) and a signal peptide (SPUL40) that acts by upregulating cell surface expression of HLA-E. Detailed characterization of SPUL40 revealed that the N-terminal 14 aa residues bestowed TAP-independent upregulation of HLA-E, whereas C region sequences delayed processing of SPUL40 by a signal peptide peptidase-type intramembrane protease. Most significantly, the consensus HLA-E-binding epitope within SPUL40 was shown to promote cell surface expression of both HLA-E and gpUL18. UL40 was found to possess two transcription start sites, with utilization of the downstream site resulting in translation being initiated within the HLA-E-binding epitope (P2). Remarkably, this truncated SPUL40 was functional and retained the capacity to upregulate gpUL18 but not HLA-E. Thus, our findings identify an elegant mechanism by which an HCMV signal peptide differentially regulates two distinct NK cell-evasion pathways. Moreover, we describe a natural SPUL40 mutant that provides a clear example of an HCMV clinical virus with a defect in an NK cell-evasion function and exemplifies issues that confront the virus when adapting to immunogenetic diversity in the host.
Gesehen am 28.11.2018